Pengaruh Pendidikan dan Pengalaman Kerja Terhadap Kinerja Karyawan Di PT Elokuensi Harapan Bangsa - M Mushlih Fadhulloh; Gregorius Duli L; Budi Ariyanto (Journal Management SMC, 2022)
ABSTRACT The purpose of this study was to determine the effect of education and work experience on employee performance at CV. Bakti Nusantara Gems. The research method used is the survey method. Data analysis method is done by using linear regression analysis. From the results of multiple regression analysis carried out in predicting the effect of education variables (X1) and work experience (X2) on employee performance (Y), it is known that the educational regression coefficient is 0.056 and the work experience regression coefficient is 0.105, and the coefficient of determination is 0.002 or 0.02%. The desired increase in employee performance can be explained or improved through increasing the education and work experience variables of employees together, however, the regression coefficient value is more dominant that affects employee performance at CV Permata Bakti Nusantara. F count 1.038 < F Table 3.191 and significance value 0.362 > 0.05 Then Ha is accepted or H0 is rejected. The results of the hypothesis test concluded that there was a positive and insignificant effect on education and work experience on employee performance. Keywords: Education, Work Environment, Motivation, Employee Performance.